Redesigning Fashion: An Analysis and Categorization of Women's Clothing Upcycling Behavior. (4th May 2017) - Janigo, Kristy A.; Wu, Juanjuan; DeLong, Marilyn
Abstract: Upcycling used clothing could transform textile waste into raw materials for new fashion items. Our research goals were to add a longitudinal element to previous research which engaged female focus group participants in a collaborative upcycling project, to further understand motivations for upcycling used clothing, and to identify common characteristics of those who choose to upcycle. Upcycling behavior of 30 women (mean age 44, 87% Caucasian) was explored through questionnaires, in-depth interviews, and visual analysis. The study also aimed to determine the conditions under which upcycling used clothes might be most successful and to further study potential for a service or business. The findings will have practical implications for those interested in fostering sustainable best practices in clothing and for entrepreneurs to weigh the pros and cons of starting a new upcycling business.